A STUDY OF THE OPTICAL PARAMETERS OF CdS THIN FILMS PREPARED BY THERMAL EVAPORATION - Shadia Ikhmayies (Journal of Amasya University the Institute of Sciences and Technology)
Cadmium sulfide is an interesting material for the use in solar cells as a window layer and in the manufacture of optoelectronic devices. The optimization of the optical parameters of this material is an important step in developing such uses. In this work polycrystalline cadmium sulfide (CdS) thin films with the same thickness (300 nm) are prepared on glass substrates at ambient temperature using the thermal evaporation technique. X-ray diffraction (XRD) revealed that the films mainly display a cubic (zinc blind) structure. The transmittance of the films is measured at room temperature in the wavelength range (290–1100 nm) and used to infer the optical parameters. The extinction coefficient ( ), refractive index ( ), the real and imaginary parts of the dielectric constant ( and ), and the dielectric energy loss ( ) are investigated. The dispersion parameters such as Eo (single-oscillator energy) and Ed (dispersive energy) of the deposited films are determined too.